(untitled) (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This research is motivated by the unknown how the development of pencak silat sport achievements in Padepokan Tanpa Bayangan Magetan based on SWOT analysis. This study aims to describe the development of pencak silat sporting achievements in Padepokan Tanpa Bayangan Magetan based on SWOT analysis. Materials and methods. This research is a descriptive research with survey type and qualitative approach. The research subjects were 15 people, consisting of administrators, coaches, and athletes of Padepokan Tanpa Bayangan Magetan. This research instrument uses an open questionnaire and uses the help of equipment such as mobile phones, cameras, recorders, stationery, and notebooks to support the course of research. Data collection techniques using interview techniques, observation, and documentation. Results. 1) The most prominent strength is that the management facilitates all the needs of athletes and funding that is already smooth and able to be managed optimally. 2) Weaknesses are on the training ground in an open or outdoor room. 3) Opportunities that exist are championships that are starting to be regularly competed. 4) The worrying threat is that there are concerns that the regeneration of athletes is hampered. Conclusion. The results of this study are that in terms of quantity, there are more strengths than weaknesses and more opportunities than threats. The preparation of strategies using the SWOT matrix produces several alternative strategies that can be applied. One strategy that can be applied is to maintain and improve the quality and achievements of athletes, then look for additional donors or new sponsors.